Cross-context qualitative synthesis of a mobile obstetric referral emergency system (MORES) in Ghana and Liberia - Camilla Bjelland; Joseph Sieka; Veronica Millicent Dzomeku; HaEun Lee; Wahdae-Mai Harmon-Gray; Emmanuel K. Nakua; Jody R. Lori (PLoS ONE, 2026)
Background To address the delayed provision of obstetric emergency care in Ghana and Liberia, our team previously implemented a mobile obstetric emergency referral system (MORES) connecting rural health facilities (RHFs) and district hospitals through a South-South-North triangular collaboration. This secondary qualitative data analysis aimed to synthesize the perceived barriers and benefits associated with the adoption of MORES in Ghana and Liberia. To guide this cross-context synthesis, we utilized Rogers’ Diffusion of Innovation Theory. Methods The analysis included individual interviews conducted among 29 district hospital providers and 33 rural health facility (RHF) workers in Liberia. In Ghana, 11 midwives at a district hospital participated in a focus group discussion. The codes were developed utilizing an inductive process. Thematic analysis was utilized to compare adoption across countries through the Diffusion of Innovation Theory. Findings Four themes were identified from the healthcare workers in Ghana and Liberia: compatibility, relative advantage, resource barriers, and limited implementation. According to healthcare workers, MORES was compatible with everyday workflow and had significant relative advantage, contributing positively to adoption. Healthcare workers were able to prioritize patient conditions upon presentation with increased referral information. Resource barriers and the limited implementation across districts restricted widespread adoption of MORES. Healthcare workers in both countries cited inconsistent access to ambulances as a barrier to complete obstetric referrals and in Liberia, the need for financial support for data and network connectivity was referenced. There were nuances by country, within the four themes. In Ghana, providers used MORES to facilitate follow-up on patients who did not complete referrals, contributing to MORES’ relative advantage. Conclusions MORES has the potential to reduce obstetric emergency referral delays in Ghana and Liberia. If the resource barriers and limited implementation of MORES are addressed, healthcare workers may continue to adopt and use the MORES system. Policy makers can address referral delays through the scale up of MORES, a compatible intervention with great relative advantage.